ANALISIS PESERTA DIDIK YANG SELF-EFFICACY AKADEMIK RENDAH PADA PEMBELAJARAN DARING SMPN7 SUIRAYA TAHUN 2021/2022 - Sidik, Ardo Saputra; Yuline, Yuline; Putri, Amallia (Universitas Tanjungpura, 2023)
This study aims to find out why academic self-efficacy is low in online learning for students. The method used is descriptive qualitative. In this study, the data sources were two class VII students of SMPN 7 Sui Raya. The data collection techniques used in the research were interviews and closed questionnaires and the data collection tools were the researchers themselves. Based on the results of the research, the two research subjects had low academic self-efficacy in online learning. (1) the characteristics of students include not being confident in their abilities, rarely participating in online learning, not being able to do the tasks given, and not understanding the material presented, (2) Factors that influence low academic self-efficacy include assignments given too much, give up easily, and lack self-confidence, (3) The impact of low academic self-efficacy includes dizziness and stress, getting reprimanded, missing material/lessons, getting low grades, and not meeting the grade promotion criteria, (4) The counseling teacher's efforts to increase academic self-efficacy include individual counseling and home visits. It was concluded from the two research subjects that the first dominant subject showed the factors that influenced his low academic self-efficacy indicated by his lack of confidence in his ability to do excessive assignments while the second subject dominantly showed feelings of insecurity in dealing with problems when learning online.